2018
DOI: 10.1039/c7nj05124g
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-doped Zn(O,S)/Ga2O3 nanoheterojunction composites for enhanced hydrogen production

Abstract: Cobalt-doped Zn(O,S)/Ga2O3 nanoheterojunction composites with different Co contents were synthesized and characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…This made the lattice of ZnS to shrink and resulted in the formation of a zinc oxysulfide (Zn­(O,S)) solid solution . As can be seen in Figure b, the doping of Co at the cation site of the Zn­(O,S) nanocatalyst caused continuous peak shifting to a slightly higher 2θ value, which agreed with our previous work . Besides, it was found that the doping of Co at 2.5% induced the maximum shift, indicating the most optimum dopant amount of Co into the Zn­(O,S) lattice.…”
Section: Results and Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This made the lattice of ZnS to shrink and resulted in the formation of a zinc oxysulfide (Zn­(O,S)) solid solution . As can be seen in Figure b, the doping of Co at the cation site of the Zn­(O,S) nanocatalyst caused continuous peak shifting to a slightly higher 2θ value, which agreed with our previous work . Besides, it was found that the doping of Co at 2.5% induced the maximum shift, indicating the most optimum dopant amount of Co into the Zn­(O,S) lattice.…”
Section: Results and Discussionsupporting
confidence: 88%
“…34−37 For the O 1s XPS spectrum plotted in Figure 5c, the respective peaks of adsorbed oxygen (O ads ), oxygen vacancy site (O v ), and oxygen in the lattice (O L ) presented at binding energy values of 533.3, 532.3, and 531.2 eV, respectively, were in accordance with the reported works. 28,38,39 The related peaks of metal−sulfur bonds and sulfide species were indicated by the S 2p 1/2 (162.8 eV) and S 2p 3/2 (162 eV) orbitals, as shown in Figure 5d, which show good agreement with the literature. 40 As previously mentioned in XRD and EDS analyses, XPS results also proved that Co had been doped into Zn(O,S) lattices to form Co−oxide and Co−sulfide chemical bonds.…”
Section: Electron Microscopysupporting
confidence: 87%
See 1 more Smart Citation
“…A green chemical conversion utilizing the photocatalysis method is an essential application for industries to promote environmentally benign chemical conversion with a crucial fundamental of chemistry [3h] . The basic photocatalytic reaction is oxidation and reduction with photo‐generated hole and electron, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…radical to oxidize many toxic organics [5] . In the other case, the photocatalytic reduction is also useful for chemical conversions, such as converting toxic 4‐nitrophenol (4‐NP) to a useful 4‐aminophenol (4‐AP) chemical without using reducing agents in a mild condition [3h,6] . Most of the works for the 4‐NP‐to‐4‐AP conversion, the common NaBH 4 or NH 4 HCO 2 as hydrogen sources are utilized to accelerate the reduction reaction [1,19] .…”
Section: Introductionmentioning
confidence: 99%